Evaluation of Knowledge, Attitudes, and Perceptions of Pharmacovigilance (PV) amongst Health Professionals and Students - Jamal Elbakay Elbakay; Omaro A. Aburas; Emhamed Boras; Salwa Muftah Eljamay; Shahrazad Eteer; Boshra Algandouz; Shahed Muftah (CV. Literasi Indonesia, 2023)
Pharmacovigilance (PV) and drug safety remain important areas of study worldwide. Unfortunately, medical professionals and students generally do not understand the reporting of PVs and adverse drug reactions (ADRs). This study compares student knowledge, attitudes, and perspectives with those of healthcare professionals in the pharmacy, medical, dental, and nursing fields. A questionnaire study was conducted to determine the level of understanding and attitudes toward PV and ADR reporting among 82 healthcare professionals (52 pharmacists, 15 physicians, 10 dentists, and 5 nurses) and 100 undergraduate healthcare students (45 pharmacies, 12 physicians, 35 dentists, and 8 nurses). According to the survey, among medical professionals and students, pharmacists are better educated about pharmacovigilance and adverse drug reactions than physicians, dentists, and nurses. The study found that pharmacists had a more favorable attitude toward pharmacovigilance and ADR reporting than other healthcare professionals. Doctors and medical students ranked second in terms of understanding of pharmacovigilance and the ADR reporting system, followed by dentists and dental students, and nurses and nursing students ranked last. In conclusion, pharmacists and pharmacy students exhibited superior knowledge, attitudes, and views of PV and ADR reporting compared to other healthcare professionals and students. The paper underlines the necessity of integrating pharmacovigilance education into the Libyan healthcare system and school curricula to train staff and educate students for real-world practices and workplaces.